Managing Co-Authorship as a Competence of Academic Writing: Organizational and Legal Points - M. A. Safonova; A. A. Safonov (Moscow Polytechnic University, 2020)
Working on projects in co-authorship rather than individually is becoming an increasingly attractive option for many members of the Russian academic community. The reasons lie in the fact that collaboration allows reducing administrative, financial, and temporal expenses. For instance, the recent events concerning the coronavirus require prompt and effective methods of exchanging data to publish works on medicine and microbiology, without arousing any disputes of an organizational or legal kind. Embracing a broad area of linguistic and cultural knowledge, academic writing can also intend to develop people's awareness of such problems as models of co-authorship, horizontal and vertical types of academic co-operation, functions assigned to members of collaborative groups at different stages of writing and publishing a text, whole ownership and that of individual contributions. The ambiguous interpretation of the concept 'creative contribution' provided by the Civil Code of the Russian Federation often impedes cooperation among co-authors, which demonstrates the need to consider legal and organizational points concerning co-publications in academic writing courses, the goal being to prevent future co-authors from potential conflicts and assisting them in managing their work efficiently.